Alternating current response and visualization of electrorheological fluid. (January 2020) - Bauerochs, Tobias; Huo, Xiaoye; Yossifon, Gilad; Ulrich, Stephan; Schneider, Steffen; Bruns, Rainer
The electrorheological effect produced by an ER-Fluid with an applied electric field is not yet fully understood. However, it is significant to understand how the viscosity increases, and thus, the ER-Effect works to optimally design ER-Applications. In this article, the ER-Effect and its response to different voltage forms with varying frequencies within a miniature fluidic device are described and visualized using a microscope. The different pressure drops across the channel are measured. Problems such as long saturation times using microchannels in combination with low flow velocities are described and explained. An electric frequency dependence of the chain formation has been discovered and that the use of alternating current offers superior performance in comparison with direct current. The optimal operating point for achieving the largest possible pressure difference is from 5 to 10 Hz for square wave voltages. In this frequency range, the performance of the electrorheological effect is greater than using direct current. From approximately 10 Hz, the power decreases with increasing electric frequency. Above 20 Hz, direct current is superior to alternating current voltage, so is not recommended for use in this range.